Simplify each of the problems.

a·a²·a³

(6x²)(-3x⁵)

(3x³)(3x⁴)(-3x²)

18c³ ÷ -3c²

9a³b⁵ ÷ -3ab²

(x²)⁷

(-2x⁴)⁵

8x⁰

6x·3x⁵·x⁰

Respuesta :

Answer:

[tex]a^{6}[/tex]

-18 [tex]x^{7}[/tex]

-27 [tex]x^{9}[/tex]

-6 [tex]c^{1}[/tex]

-3 [tex]a^{2} b^{3}[/tex]

[tex]x^{14}[/tex]

-32 [tex]x^{20}[/tex]

8

6x .3x^{5} . x⁰    = 18 x^{6}

Step-by-step explanation:

[tex]a^{6}[/tex]

-18 [tex]x^{7}[/tex]

-27 [tex]x^{9}[/tex]

-6 [tex]c^{1}[/tex]

-3 [tex]a^{2} b^{3}[/tex]

[tex]x^{14}[/tex]

-32 [tex]x^{20}[/tex]

8

6x .3x^{5} . x⁰  =   = 18 x^{6}

When we multiply powers then they get added like in the first question.

When they are powered further then they're multiplied.

Answer:

1) a. a² a³ = a⁶

2) (6[tex]x^{2}[/tex] ) (-3[tex]x^{5}[/tex] )  =  -18 [tex]x^{7}[/tex]

3)  (3[tex]x^{3}[/tex] ) (3[tex]x^{4}[/tex] ) (-3[tex]x^{2}[/tex] ) =      =-27 [tex]x^{9}[/tex]

4)  18c³ ÷ -3c²  =  -6c

5) 9a³b⁵ ÷ -3ab² =      = -3 a²b³

6) ( [tex]x^{2}[/tex] )⁷ =  [tex]x^{9}[/tex]

7) ( -2 [ [tex]x^{4}[/tex] ] )⁵ =   = -2 [tex]x^{9}[/tex]

8) 8x⁰ = 8

9) 6x .3[tex]x^{5}[/tex] . x⁰  =   = 18 [tex]x^{6}[/tex]

 Step-by-step explanation:

1) a . a².a³

= a¹ x a²x a³

= a¹⁺²⁺³

= a⁶

2) (6[tex]x^{2}[/tex] ) (-3[tex]x^{5}[/tex] )

   = -18 [tex]x^{2+5}[/tex]

    =  -18 [tex]x^{7}[/tex]

3) (3[tex]x^{3}[/tex] ) (3[tex]x^{4}[/tex] ) (-3[tex]x^{2}[/tex] )

    = -27 [tex]x^{3+4+2}[/tex]

    =-27 [tex]x^{9}[/tex]

4) 18c³ ÷ -3c²

    =  - [tex]\frac{18}{3}[/tex] c

     =  -6c

5) 9a³b⁵ ÷ -3ab²

    = -3 a²b³

6) ( [tex]x^{2}[/tex] )⁷

 =

[tex]x^{9}[/tex]

7) ( -2 [ [tex]x^{4}[/tex] ] )⁵

 = -2 [tex]x^{9}[/tex]

8) 8x⁰ = 8 x 1 = 8

9) 6x .3[tex]x^{5}[/tex] . x⁰

  = 18 [tex]x^{1+5+0}[/tex]

9) 6x .3[tex]x^{5}[/tex] . x⁰

 = 18 [tex]x^{6}[/tex]

ACCESS MORE